How common are complications following polypropylene mesh, biological xenograft and native tissue surgery for pelvic organ prolapse? A secondary analysis from the PROSPECT trial. (27th September 2021) - Reid, FM; Elders, A; Breeman, S; Freeman, RM; ,
Abstract : Objective: To report complication rates following prolapse surgery using polypropylene mesh inlay, polypropylene mesh kit, biological collagen xenografts and native tissue repairs. Design: Secondary analysis of the PROSPECT randomised controlled trial and cohort study. Setting: Thirty‐five UK hospitals. Population: A total of 2632 women undergoing anterior and/or posterior vaginal prolapse repair. Methods: Event rates were calculated for all complications. Analysis was by treatment received. Main outcome measures: IUGA/ICS classification of complications and validated patient reported outcome measures. Results: At baseline, 8.4% of women had 'generic' pain/discomfort; at 2 years following surgery, there was an improvement in all four groups; however, 3.0% of women developed de novo extreme generic pain. At 24 months de novo vaginal tightness occurred in 1.6% of native tissue, 1.2% of biological xenograft, 0.3% of mesh inlay and 3.6% of mesh kit. Severe dyspareunia occurred in 4.8% of native tissue, 4.2% of biological xenograft, 3.4% of mesh inlay repairs and 13.0% of mesh kits. De novo severe dyspareunia occurred in 3.5% of native tissue, 3.5% of biological xenograft, 1.4% of mesh inlays and 4.8% of mesh kits. Complications requiring re‐admission to hospital, unrelated to mesh, affected 1 in 24 women; the most common reasons for re‐admission were vaginal adhesions, urinary retention, infection and constipation. Conclusions: This is the first study to address the complications of vaginal mesh used for prolapse surgery alongside data from both native tissue and biological xenograft. It demonstrates the complexity of assessing pain and that all types of prolapse surgery have low surgical morbidity and a low rate of severe complications. Tweetable abstract: A prospective study of 2362 women undergoing vaginal mesh, xenograft or native tissue repair found low surgical morbidity and low rates of severe complications. Tweetable abstract: A prospective study of 2362 women undergoing vaginal mesh, xenograft or native tissue repair found low surgical morbidity and low rates of severe complications.